Bibliographic and visualized analysis of geopolymer research and its application in heavy metal immobilization: A review. (1st February 2019) - Ji, Zehua; Pei, Yuansheng
Abstract: Geopolymer (GP) is a novel aluminosilicate inorganic polymer, and it possesses excellent characteristics in application of various fields, and its advantages have attracted worldwide attention. Based on the Citespace software, the bibliometric analysis combined with the visualization analysis on GP was summarized on the publications that extracted from Web of Science (WOS) from 1990 to 2017. The analysis results demonstrate that the research on GP develops rapidly in the last years, and the GP have already possessed a degree of application value in several engineering fields. This research shows a multidisciplinary amalgamation tendency in contents and methods. Additionally, the main application in pollution treatment of GP is heavy metal immobilization. The immobilization effects of GP for heavy metal are mainly depended on physical encapsulation, adsorption effect, chemical bonding, substitution for Al3+ and other effects. And these effects are simultaneous action on heavy metal immobilization under different conditions. Furthermore, the majority of GP are based on the fly ash and metakaolin, and the most frequently used leaching method is the Toxicity Characteristic Leaching Procedure (TCLP). Moreover, there are also several problems need to be solved before GP can be widely applied in heavy metal treatment. Overall, GP have possessed a great potential research and application value in the present stage, especially in the aspect of heavy metal immobilization. Graphical abstract: Image 1 Highlights: Reviewed the research origins, formation mechanism and application advantages of geopolymer. The scientometric review of scientific literature relating to geopolymer research in 1990–2017 was conducted. Five heavy metal immobilization mechanisms and latest application of geopolymer were summarized. The existing problems of geopolymer in heavy metal immobilization were discussed.